2004
DOI: 10.1152/physrev.00013.2003
|View full text |Cite
|
Sign up to set email alerts
|

Functional Diversity of Protein Phosphatase-1, a Cellular Economizer and Reset Button

Abstract: Ceulemans, Hugo, and Mathieu Bollen. Functional Diversity of Protein Phosphatase-1, a Cellular Economizer and Reset Button. Physiol Rev 84: 1–39, 2004; 10.1152/physrev.00013.2003.—The protein serine/threonine phosphatase protein phosphatase-1 (PP1) is a ubiquitous eukaryotic enzyme that regulates a variety of cellular processes through the dephosphorylation of dozens of substrates. This multifunctionality of PP1 relies on its association with a host of function-specific targetting and substrate-specifying prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
594
0
22

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 604 publications
(631 citation statements)
references
References 418 publications
(330 reference statements)
15
594
0
22
Order By: Relevance
“…Previously, both GSK3β [32] and PP1 [5] were shown to regulate the expression and activity of SERCA2, respectively. Therefore, we tested if the inhibition of GSK3 pharmacologically or through the inhibition of PP1 with I-2 would affect SERCA2 levels in SH-SY5Y cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, both GSK3β [32] and PP1 [5] were shown to regulate the expression and activity of SERCA2, respectively. Therefore, we tested if the inhibition of GSK3 pharmacologically or through the inhibition of PP1 with I-2 would affect SERCA2 levels in SH-SY5Y cells.…”
Section: Resultsmentioning
confidence: 99%
“…While protein kinases take part in phosphorylation, protein phosphatases catalyse the dephosphorylation of proteins, thereby exerting a fundamental role in regulating cellular processes (Dickman & Yarden, 1999). It has been suggested that about one-third of the eukaryotic proteins are regulated by reversible phosphorylations of specific serine, threonine and/or tyrosine residues (Ceulemans & Bollen, 2004). To date, the major group of serine/threonine protein phosphatases are encompassed by two different structural families.…”
Section: Discussionmentioning
confidence: 99%
“…Protein phosphatases catalyse the dephosphorylation of specific substrates that are important for processing various biological and cellular functions (Ceulemans & Bollen, 2004;Dickman & Yarden, 1999;Hunter, 1995), and this catalytic action is known to de-activate signalling pathways induced by a variety of protein kinases (Hunter, 1995). In Arabidopsis, for instance, protein phosphatase type 2C is involved in the negative regulation of the abscisic acid signalling pathway (Saez et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…p68 possesses a variant of the RVXF motif by which PP1 binds to its various targeting subunits [Zhao and Lee, 1997]. The actions of PP1 are restricted to the vicinity of its microenvironment, so that its cellular functions are dictated by its localization via these targeting subunits [Barford et al, 1998;Ceulemans and Bollen, 2004]. This argues that binding of PP1 to p68 functions to regulate phosphorylation states of Pol d itself or of its neighbors within the replication machinery.…”
Section: Regulation Of Pol D Activity By Protein Phosphorylationmentioning
confidence: 99%